1975
DOI: 10.1111/j.1600-0773.1975.tb00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Interaction of Ethanol and Alprenolol in Isolated Liver Cells

Abstract: Metabolism of ethanol and alprenolol was studied in isolated rat liver cells. At low ethanol concentrations, where the rate of ethanol metabolism seemed to be limited by the rate of re-oxidation of NADH, ethanol metabolism was markedly stimulated by the addition of alprenolol, propranolol or hexobarbital. At higher concentrations of ethanol no stimulation by added alprenolol was observed. Alprenolol-stimulated ethanol metabolism was more sensitive to low concentrations of the ADH inhibitor 4-CHs-pyrazole, than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
1986
1986

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Therefore t h e effect of substrates which may enhance the hepatic concentration of acetyl-CoA was studied with respect t o influence on d r u g acetylation. Since isolated rat liver cells have been shown t o perform drug acetylation ( M e r l a n d & Olsen 1977;Suolinna 1980), a n d also to be suitable in studying factors which may influence d r u g metabolism (Grundin 1975;Notten et al 1975;Bridges & F r y 1977), this system was chosen a s model system for t h e present study.…”
mentioning
confidence: 99%
“…Therefore t h e effect of substrates which may enhance the hepatic concentration of acetyl-CoA was studied with respect t o influence on d r u g acetylation. Since isolated rat liver cells have been shown t o perform drug acetylation ( M e r l a n d & Olsen 1977;Suolinna 1980), a n d also to be suitable in studying factors which may influence d r u g metabolism (Grundin 1975;Notten et al 1975;Bridges & F r y 1977), this system was chosen a s model system for t h e present study.…”
mentioning
confidence: 99%
“…also very little inhibitory effect on drug oxidation in these cells (GRUNDIN 1975). The effect of rotenone on p-nitroanisole metabolism in the isolated liver cells was not very pronounced, there was, however, a significant decrease in the amount of conjugated products with a concomitant increase in the amount of free phenol (fig.…”
Section: -0 Glucuronide5mentioning
confidence: 89%
“…1970). In isolated liver cells, on the other hand, ethanol stimulated these reactions at low concentrations ( 5 mM) but was inhibitory at higher concentrations (GRUNDIN 1975). The glucuronidation of p-nitrophenol in microsomes was inhibited to only a minor extent even at concentrations up to 100 mM.…”
Section: A-amentioning
confidence: 91%
“…Interactions with drug metabolism have been studied in suspensions of purified parenchymal cells (GRUNDIN 1975;MOLDEUS et al 1976), but never in mixed cell suspensions. We decided to use primary suspensions for further studies because they were shown to metabolize antipyrine at a rate equal to purified parenchymal cells, and also because they are most easy to prepare.…”
Section: Discussionmentioning
confidence: 99%
“…and to be useful in the study of short term drug-drug metabdic interactions (VON BAHR etal. 1974;MOLDEUS et al 1976;GRUNDIN 1975;ERICSON & HOLTZMAN 1976; SCOTT HAYES & BRENDEL 1976). One major advantage provided by dilute suspensions of liver cells is that the metabolism of drugs can be studied as the only mechanism responsible for alterations in drug concentrations measured.…”
Section: Frymentioning
confidence: 99%